Ovarian reserve and IVF outcomes in patients with inflammatory bowel disease: A systematic review and meta-analysis. (August 2022) - Sun, Honghao; Jiao, Jiao; Tian, Feng; Liu, Qing; Bian, Jiansu; Xu, Rongmin; Li, Da; Wang, Xiuxia; Shu, Hong
Summary: Background: Inflammatory bowel disease (IBD) mainly affects people during reproductive age. However, it is unclear whether IBD might be associated with impaired ovarian reserve in female patients or with in vitro fertilization (IVF) outcomes. Methods: This systematic review and meta-analysis included articles from inception to May, 2022. Random-effect model was applied to calculate the standardized mean differences (SMDs) and odds ratios (ORs) and their 95% confidence intervals (95%CIs). Studies comparing the ovarian reserve or IVF outcomes of patients with IBD with the population were considered. To be included in this study, necessary measurements such as OR, relative risk (RR), SMD or hazard ratio (HR) or any necessary information to calculate them were provided in the articles. Letters, case reports, review articles including meta-analyses and expert opinions were excluded. For different articles studying the same population, the article with larger scale was selected. Findings: We included in our analysis 9 studies and data from 2386 IBD records and matched controls. Comparing with women without IBD, women with IBD had lower anti-mullerian hormone (AMH) levels (SMD = -0.38, 95%CI: -0.67, -0.09); (I 2  = 79.0%, p = 0.000). Patients with IBD of different ages showed distinct ovarian reserves, with patients below 30 years old not showing any decline in ovarian reserve compared to the control group (SMD = -0.56, 95%CI: -2.28, 1.16); (I 2  = 96.3%; p = 0.000), while patients with IBD over 30 years old (SMD = -0.75, 95%CI: -1.07, -0.43); (I 2  = 0.0%; p = 0.608) showed a decline compared to control group. Patients with IBD in remission stage had similar ovarian reserves to population (SMD = -0.10, 95%CI: -0.32, 0.12); (I 2  = 0.0%; p = 0.667), while patients in active stage showed an impaired ovarian reserve (SMD = -1.30, 95%CI: -1.64, -0.96); (I 2  = 0.0%; p = 0.318). Patients with IBD showed a pregnancy rate after receiving IVF treatment comparable to the control population (OR = 0.87, 95%CI: 0.55, 1.37); (I 2  = 70.1%, p = 0.035). Interpretation: The result of this study suggest that IBD may reduce reproductive age women's ovarian reserve and IVF treatment might help pregnancy outcomes in patients with impaired fertility. These results should be further validated in additional studies given the heterogeneity and quality of the studies included. Funding: This study was supported by the National Natural Science Foundation of China (No. 81671423), National Key Research and Development Program of China (No. 2016YFC1000603), 2020 Shenyang Science and Technology Plan Program (No. 20-205-4-006), Scientific and Technological Talents Applied Technology Research Program of Shenyang (No. 18-014-4-56).